Pengaruh Etika, Pengalaman Auditor, dan Situasi Audit Terhadap Ketepatan Pemberian Opini Akuntan Publik di Jakarta Selatan - Andhika Aria Bhava; Nofryanti, Nofryanti (Lembaga Pengembangan Kinerja Dosen, 2026)
The purpose of this study is to examine the influence of ethics, auditor experience, and audit situations on the accuracy of giving audit opinion issued by public accountants in South Jakarta. The population in this study consists of auditors working at public accounting firms, particularly those located in South Jakarta. The sample used includes 42 respondents, selected using a purposive sampling method. The data source in this study was obtained through a data collection technique in the form of a questionnaire. This research employs multiple linear regression analysis. The analysis result from public accounting firms in South Jakarta indicate that the audit situation has a significant influence on the accuracy of giving audit opinion. Meanwhile, ethics and auditor experience has no significant influence on the accuracy of giving audit opinion.